Younger supervisors, older subordinates: An organizational‐level study of age differences, emotions, and performance. (4th September 2016) - Kunze, Florian; Menges, Jochen I.
Summary: Younger employees are often promoted into supervisory positions in which they then manage older subordinates. Do companies benefit or suffer when supervisors and subordinates have inverse age differences? In this study, we examine how average age differences between younger supervisors and older subordinates are linked to the emotions that prevail in the workforce, and to company performance. We propose that the average age differences determine how frequently older subordinates and their coworkers experience negative emotions, and that these emotion frequency levels in turn relate to company performance. The indirect relationship between age differences and performance occurs only if subordinates express their feelings toward their supervisor, but the association is neutralized if emotions are suppressed. We find consistent evidence for this theoretical model in a study of 61 companies with multiple respondents. Copyright © 2016 John Wiley & Sons, Ltd.